Analisa Ratio lancar Dan Perputaran Piutang Terhadap Tingkat Pengembalian Asset Bisnis Makanan Dan Minuman Yang Tercatat Di Pasar Modal Indonesia - Nasution, Yuslinda; Sawitry, Ina; Noviarti (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
The research aims to evaluate the impact of the current ratio and accounts receivable turnover on the return on assets of the Food and Beverage business on the Indonesian Capital Market (BEI) for the 2019 - 2022 period separately and together. The research population consisted of 84 companies and 24 companies were sampled using certain consideration methods (criteria). The test results explain that current assets have a directly proportional impact on the level of return on assets, where the t table (3.272 ≥ 1.98552) is at a significance level of 0.002. Meanwhile, receivables turnover also individually influences ROA, with t table results (2.142 ≥ 1.98552) with a significance level of 0.035. Overall, the current ratio and receivables turnover have an influence on ROA of 6.957 at a significance level of 0.002. The results of the coefficient of determination (R2) show that the influence of the current ratio and receivables turnover on ROA is 0.111, indicating that 11% of the variation in ROA can be explained by these two variables. . And 89% are outside the variables studied. Keywords: Current Ratio, Receivables Turnover, ROA